Tissue distribution and health risk of trace elements in East Asian finless porpoises. (1st December 2021) - Tian, Jiashen; Gan, Zhiwei; Sanganyado, Edmond; Lu, Zhichuang; Wu, Jinhao; Han, Jiabo; Liu, Wenhua
Abstract: We investigated the tissue distribution, trophic transfer, and ecological risk of 13 trace elements in 26 East Asian finless porpoises ( Neophocaena asiaeorientalis sunameri ), an endangered species found in the Liaodong Bay and the north Yellow Sea. All the investigated trace elements were detected in the tissue and food web of the East Asian finless porpoises. The concentrations of the potentially toxic elements were 2.37 × 10 −5 – 754 mg kg −1 dry weight (dw) in stranded porpoises and 0.01–159 mg kg −1 dw in their food web. Tissue-specific distribution of the trace elements generally ranked as: liver > kidney > heart > lung > muscle. Zn was the dominant contaminant in the five investigated tissues. Significant positive correlations were found between body length or age and some trace elements, especially Cd. Adults (≥2 years old) presented higher concentrations of most of the trace elements than juveniles (<2 years old). Sex-dependent distribution of the trace elements was insignificant except for Mn, Ni, and Zn in muscle and renal tissue. As, Cu, Mn, Ni, Pb, and V biodiluted across the East Asian finless porpoise food web while Zn biomagnified. However, Hg, Cd, Co, Cr, Se, and Sn did not exhibit apparent trophic transfer trends. Overall, ecological risk assessment of trace elements in East Asian finless porpoises suggested that greater attention should be given to Hg, As, Cd, and Se. Graphical abstract: Image 1 Highlights: Trace elements accumulation ranked liver > kidney > heart > lung > muscle. Muscular Mn and renal Mn and Zn were higher in female porpoise than in males. Renal Ni was lower in females than males probably due to maternal transfer. As, Cu, Mn, Ni, Pb, and V biodiluted across coastal food web while Zn biomagnified. Ecological risk assessment revealed Hg, As, Cd, and Se require greater attention.